If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(t + -2) + 11 + -4 = 2t + 3 Reorder the terms: 4(-2 + t) + 11 + -4 = 2t + 3 (-2 * 4 + t * 4) + 11 + -4 = 2t + 3 (-8 + 4t) + 11 + -4 = 2t + 3 Reorder the terms: -8 + 11 + -4 + 4t = 2t + 3 Combine like terms: -8 + 11 = 3 3 + -4 + 4t = 2t + 3 Combine like terms: 3 + -4 = -1 -1 + 4t = 2t + 3 Reorder the terms: -1 + 4t = 3 + 2t Solving -1 + 4t = 3 + 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. -1 + 4t + -2t = 3 + 2t + -2t Combine like terms: 4t + -2t = 2t -1 + 2t = 3 + 2t + -2t Combine like terms: 2t + -2t = 0 -1 + 2t = 3 + 0 -1 + 2t = 3 Add '1' to each side of the equation. -1 + 1 + 2t = 3 + 1 Combine like terms: -1 + 1 = 0 0 + 2t = 3 + 1 2t = 3 + 1 Combine like terms: 3 + 1 = 4 2t = 4 Divide each side by '2'. t = 2 Simplifying t = 2
| 7/24-1/3 | | 4+14m-1=8m+75-3m | | 9x+3x=5x+10 | | -2w+7=3x-3 | | 12-58= | | 27+1x=23 | | 5x-(12-2x)=3x | | 7.3x-1.8=20.1 | | -b=72 | | -1x+28=18 | | 10x+180=(x+10)(x+4) | | 66y=132 | | -26+5x=24 | | 21=5m+6+5 | | 12x-2=150 | | 5h-7=12(h+1) | | 72+-5x=27 | | 3k+6.2= | | 9=30n | | x*-6=4 | | 850=1.33*x | | (8y-15)2/3=14 | | 7/5/3 | | 1061=1.71*x | | 2(h+10)=59 | | h(t)=-16t^2+32x+1.5 | | -16r=-75 | | 4/5x-1/10x=9/10x | | 5t-3=(t+7)+3t | | 2x^3-x^2+16x-9=0 | | (2x)+(x)=162 | | 48+(8x+20)=180 |